Pengaruh Partisipasi Anggaran dan Kejelasan Anggaran terhadap Kesenjangan Anggaran dengan Job Relevant Information sebagai variable moderating - Girsang, Rapika Br; Irfan , Irfan; Hani, Syafrida (CV. ITTC INDONESIA, 2024)
This study aims to test and analyze the effect of budget participation, clarity of budget targets on budgetary slack with Job Relevant Information as a moderating variable. This study was conducted at PT. Indomobil Prima Niaga Sumut Aceh (consisting of 5 branches). The sample selection method of saturated sampling is a sampling technique when all members of the population are used as samples, namely 38 samples. The sample in this study was the Head of the department consisting of Finance and Accounting Head, Aftersales Head, Branch Manager, Regional Manager and Hoyu Manager who are involved in budget preparation, budget implementation and budget accountability. The research approach used in this study is associative research. This type of research is quantitative research. Data collection was carried out using a survey method by distributing questionnaires to respondents. The analysis technique used is the Quantitative Approach Using Statistical Analysis, namely Partial Least Square - Structural Equestion Model (PLS SEM). The results of the study indicate that budget participation has an effect on budgetary slack. Furthermore, clarity of budget targets has an effect on budgetary slack. Job relevant information moderates the effect of budget participation and clarity of budget targets on budgetary slack